The prevalence of fast food consumption among undergraduates: evidence from Malaysia / Marziah Mokhtar, Sabariah Yusoff and Nur Aqilah Muhamad Murad - Mokhtar, Marziah; Yusoff, Sabariah; Muhamad Murad, Nur Aqilah (Faculty of Business and Management, UiTM Shah Alam, 2020)
The fast-food industry has been growing rapidly since its first opening in Malaysia in 1980s. The trend of consuming fast food continues to grow at a rapid rate especially among students. Therefore, the purpose of this study is to investigate various key determinants of fast-food consumption among Malaysian undergraduates as they constitute a large percentage of fast-food consumers. A set of validated questionnaires was used in gathering data on the key determinants of fast-food consumption prevalence namely consumer behaviour, personal lifestyle, and product attributes. A quantitative investigation was conducted on the data using SPSS package. Few analyses namely Descriptive, Reliability and Multiple Regression were used. The Pearson Correlation indicates product attributes have a strong correlation while there is a moderate one for both consumer behaviour and personal lifestyle. Multiple Regression Analysis results highlight that personal lifestyle and product attributes are both positively significant while consumer behaviour, which positively affects fast food consumption among the Malaysian undergraduates, is not a significant determinant.